Parent Perceptions on The Obedience in Implementing Primary Immunization to Infants Reviewed with Health Belief Model - Ni Ketut Alit Armini; Maria Roswita Loin; Aria Aulia Nastiti (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2017)
Introduction: universal coverage immunization achievements that have not reached national targets, including in Puskesmas Kualin, were only 61.5% of the 90% target by 2015. One of the causes of parents' negative perceptions of immunization. The Health Belief Model Theory describes a person's judgment in a healthy way influenced by perceptions about benefits and barriers. This study aims to explain the relationship of perception of benefits and barriers with obedience in implementing of primary immunization to infants. Methods: The study was cross-sectional with the population of mothers with infants aged 12-18 months in the working area of Puskemas Kualin. The sample size of 80 persons was selected using cluster sampling. Independent variable in the study was the perception of benefit and perception of barriers. The dependent variable was the implementation of primary immunization to infants. Data were collected using questionnaire and health monitoring card. Data analysis using Spearman Rho statistic test with significance level α ≤ 0,05. Results: There was a relationship with a positive direction between perception and obedience to the application of primary immunization to infants (p = 0.0001, r=0.428). There was a relationship with a negative direction between the perception of barriers and obedience to the application of primary immunization to infants (p=0.0001, r=-0.525). Conclusion: High perceptions of the benefits and low perceptions of parental barriers are associated with obedience to the implementation of primary immunization to infants. It is expected that parents are diligent to Posyandu every month and health workers visit home for sweeping immunization.